Implementation of Image Processing On Hydroponic Pakcoy Plants To Detect AB MIX Nutrient Levels - Rosyidah, Izzah; Anshory, Izza; Sulistiyowati, Indah; Syahrorini, Syamsudduha (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2024)
One of the current land use alternatives is cultivating vegetables using the hydroponic method. One way that must be considered to get good results when cultivating pak choy using the hydroponic method is to periodically maintain the pH level of the nutrient media in the hydroponic pak choy plant. This research aims to create a system that can detect nutrient levels and the condition of hydroponic plants. To test this, hydroponic plant nutrition was carried out using 2 types of treatment. The first treatment, hydroponic pak choy plants are given nutrition according to the optimal PPM (Parts Per Million) nutrient dose, namely in the range of 1100 to 1400 so that the leaves produced are healthy and green. Meanwhile, in the second treatment, hydroponic pakchoy plants were given less nutrition than they should be given, namely in the range of 800-1000 PPM so that the leaves produced by hydroponic pakchoy plants wilt due to lack of nutrition. The control devices used in this system include ESP32 as a microcontroller, ESP32 Cam for plant monitoring and digital image processing, pH sensors, and TDS sensors to monitor nutrients in the air. Based on the experimental results, it was found that mustard leaves will be green if the TDS meter value is at an average of 1160.83 PPM with an average error of 5.61% while the pH meter value is at 9.82 with an average error 4.2 %. The percentage value of green detected by image processing is 120.33% with a lower limit of green [35, 21, 63] and an upper limit of green [55, 255, 255]. The Esp32 cam can also process digital images of hydroponic pak choy leaves well.